Agricultural production and Indian history - Ludden, David E. (Delhi : New York : Oxford University Press, 1994)
Contributed articles.
Series statement from jacket.
Includes bibliographical references (p. [369]-382).
Keywords: Agricultural productivity -- India; Agriculture -- Economic aspects -- India; Agricultural productivity -- Social aspects -- India; Farm management -- Social aspects -- India; India -- History -- British occupation, 1765-1947.